Pengaruh Lingkungan Kerja, Kesehatan Kerja, Dan Keselamatan Kerja Terhadap Kinerja Karyawan Pada Perusahaan Daerah Air Minum Kota Malang - Nilla Uswatun Chasanah; Nurhajati Nurhajati; Pardiman Pardiman (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
AbstractThe Purpose Of This Study Was To Determine The Effect Of Work Environment, Occupational Health And Work Safety On Employee Performance In Malang Municipal Water Supply Company. The Sample In This Study Were 77 Permanent Employees. The Analytical Method Used In This Study Is Multiple Linear Regression Analysis With Hypothesis Testing Using T Test And F Test. From This Study Provides Results And Shows That There Is Simultaneously A  Influence Between Work Environment, Occupational Health And Work Safety On Employee Performance.Keywords: Work Environment, Occupational Health, And Work Safety